PROPOSALS AND ALGORITHMS FOR CRIMINAL LAW AND CRIMINAL PROCEDURE ACTIONS IN FULFILLING REQUIREMENTS OF ARTICLE 615 OF THE CRIMINAL PROCEDURE CODE OF UKRAINE - Syvodied, Ivan (Scientific Journal of Polonia University, 2023)
The article is devoted to the analysis of scientific approaches to determining the essence of criminal law and criminal procedure characteristics of offenses committed in the occupied territories of Ukraine. Attention is paid to the need to distinguish between the following scientific concepts: “criminal law characteristics of a certain type of a criminal offense”, “criminal law characteristics of a group of crimes”, and “forensic characteristics”. The problem of shaping a criminal law characteristic as a system of generalized data on the generic elements of criminal offenses, given their connections, is considered. The author emphasizes the practical significance of the relevant characteristics in managing the investigation of offenses committed in the occupied territories of Ukraine and formulating methodological recommendations for the pre-trial investigation of the specific group of criminal offences. In addition, there is a lack of аn overall study of the internal processes determining the development of foundations for specific methods of investigation of offenses in domestic criminology. Since the relevant process is natural, there is an objective need to elaborate methods for solving tasks characteristic of all cases of investigation. In that context, the author provides a list of comprehensive, in his opinion, proposals and algorithms for criminal law and criminal procedural actions in fulfilling the requirements of Art. 615 of the Criminal Code of Ukraine by prosecutors and investigators of law enforcement agencies of Ukraine.